2016
DOI: 10.2147/ott.s90801
|View full text |Cite
|
Sign up to set email alerts
|

Long-term gene therapy with Del1 fragment using nonviral vectors in mice with explanted tumors

Abstract: Cancer gene therapy using nonviral vectors is useful for long periods of treatment because such vectors are both safe and inexpensive, and thus can be used repeatedly. It has been reported that gene therapy with an E3C1 fragment of Del1 in a mouse explanted tumor model improved prognosis. The present study aimed to analyze the long-term effects of repeated non-viral gene transfer of E3C1. Mice with explanted tumors of SCCKN cells, a human squamous carcinoma, were treated with a plasmid encoding E3C1. Plasmids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Despite the compelling need for therapies for pathological fibrosis, an effective treatment is not available. Kitano et al reported that a recombinant protein with the CXDXXXXYXCXC sequence subcutaneously injected using a non-viral vector inhibited the growth of tumors transplanted in mice (14)(15)(16)(17). Their results suggested that the expressed protein was effective not only at the site of subcutaneous injection but also in distant organs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the compelling need for therapies for pathological fibrosis, an effective treatment is not available. Kitano et al reported that a recombinant protein with the CXDXXXXYXCXC sequence subcutaneously injected using a non-viral vector inhibited the growth of tumors transplanted in mice (14)(15)(16)(17). Their results suggested that the expressed protein was effective not only at the site of subcutaneous injection but also in distant organs.…”
Section: Discussionmentioning
confidence: 99%
“…Explanted tumor models were generated as described previously (14)(15)(16)(17)(18). Briefly, Nu/Nu athymic nude mice were injected subcutaneously in the right flank with squamous cell carcinoma KN (SCCKN) cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation